'Financialisation' in Post-Keynesian models of distribution and growth - a systematic review - Eckhard Hein; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
We review recent attempts to integrate 'financialisation' processes into Post-Keynesian distribution and growth models and distinguish three principal channels of influence: 1. objectives and finance restrictions of firms, 2. new opportunities for households' wealth-based and debt-financed consumption, and 3. distribution between capital and labour, on the one hand, and between management and workers on the other hand. Starting from a re-interpretation of the Post-Keynesian theory of the firm we bridge the gap between micro- and macro-analysis of 'financialisation' and we trace the main characteristics and effects of 'financialisation' from the micro to the macro level taking into account stock-flow interactions. Our review of the theoretical literature on 'financialisation' shows that expansive effects may arise under certain conditions, in particular when there are strong wealth effects in firms' investment decisions (via Tobin's q) and in households' consumption decisions. However, our review also suggests that even an expansive finance-led economy may build up major financial imbalances, i.e. increasing debt-capital or debt-income ratios, which make such economies prone to financial instability.
urn:nbn:de:101:1-20080818205
Keywords: E12; E21; E22; E25; E44; 330; Financialisation; Post-Keynesian distribution and growth models